Respuesta :
A) 8x + 9y = -3
B) 6x + 7y=1
We multiply A) by -(6/8)
A) -6x -6.75y = 2.25 then we add this to
equation B
B) 6x + 7y=1
25y = 3.25
y = 13
and X=-15
^ 5.0
Step-by-step explanation:
B) 6x + 7y=1
We multiply A) by -(6/8)
A) -6x -6.75y = 2.25 then we add this to
equation B
B) 6x + 7y=1
25y = 3.25
y = 13
and X=-15
^ 5.0
Step-by-step explanation:
Answer:
• Let's first assign identifications to the equations given:
[tex]{ \rm{8x + 9y = {}^{ - }3 \: - - - \{equation \: (a) \} }} \\ { \rm{6x + 7y = 1 - - - \{equation \: (b) \}}} \\ [/tex]
• There are various methods to solve this system of equation, namely;
- Graphical method
- Substitution method
- Elimination method
- Calculus (Calculator synthetic method)
1. Graphical method
→ You'll have to draw a graph, demacate it very well following the suitable scale.
→ Get values to plot from both equation (a) and equation (b).
→ Draw respective lines of each equation. The point of intersection of the lines is the answer of the values of x and y.
→ It'll be in coordinate format i.e; (x, y)
2. Substitution method
→ Lemme first consider equation (a)
[tex]{ \rm{8x + 9y = {}^{ - }3 }}[/tex]
• make x the subject of the equation (a):
[tex]{ \rm{8x = - 3 - 9y}} \\ \\ { \rm{x = \frac{ - 3}{8} - \frac{9}{8}y }} \: { \rm{- - - \{equation \: (c)}} \}[/tex]
→ Considering equation (b) next
[tex]{ \rm{6x + 7y = 1}}[/tex]
• substitute x in equation (b) with x in equation (c)
[tex]{ \rm{6( \frac{ - 3}{8} - \frac{9}{8}y ) + 7y = 1 }} \\ \\ { \rm{ - \frac{9}{4} - \frac{27}{4} y + 7y = 1}} \\ \\ { \rm{ \frac{1}{4} y = \frac{13}{4} }} \\ \\ { \underline{ \rm{ \: \: y = 13 \: \: }}}[/tex]
• then find x using equation (c)
[tex]{ \rm{x = \frac{ - 3}{8} - \frac{9}{8} y }} \\ \\ { \rm{x = \frac{ - 3}{8} - \frac{9}{8} (13)}} \\ \\ { \underline{ \rm{ \: \: x = - 15 \: \: }}}[/tex]
3. Elimination method:
→ Here, we have to align the equations so that if we use addition or subtraction operations we remain with one term giving us zero [ eliminated ]
→ Multiply equation (a) by 6 and multiply equation (b) by 8. In order to eliminate x
→ Then we subtract equation (a) with equation (b)
[tex]{ \underline{ \rm{ - \binom{6(8x + 9y = - 3)}{8(6x + 7y = 1)} }}} \\ { \rm{ 0x \: - 2y = - 26 }} \\ \\ { \rm{ - 2y = - 26}} \\ \\ { \underline{ \rm{ \: \: y = 13 \: \: }}}[/tex]
• find x using equation (c)
[tex]{ \rm{x = \frac{ - 3}{8} - \frac{9}{8} y}} \\ \\ { \underline{ \rm{ \: \: x = - 15 \: \: }}}[/tex]
4. Calculator synthetic method:
→ To use this method, you must have a scientific calculator.
→ If you have it, follow the steps below;
- Go to mode (press it 3 times until you see "EQN" )
- Press 1 or any number below the "EQN". It'll display "Unknowns" with 2 and 3 below it. 2 → Two equations system. 3 → 3 equations system.
- According to our question, it is a two equations system, press 2
- It'll display a, b and c [ a is the coefficient of x, b is the coefficient of y, c is the constant]
- For a1 press 8 then press "equal sign", b1 press 9, then equal sign, c1 press -3 then equal sign.
- Follow the same procedure for a2, b2 and c2
- Automatically, It will display the answers
Answer: x = -15, y = 13